The big chill [videorecording (DVD)] - Kasdan, Lawrence, 1949-; Goldblum, Jeff, 1952-; Hurt, William; Place, Mary Kay; Kline, Kevin (Columbia TriStar Home Video, 1998)
Seven college housemates from the 1960s who have drifted apart reunite at the funeral of a friend. Having entered adulthood as non-conformists, most now belong to the establishment. Stunned by the death of their peer, sensing their own mortality and the loss of their innocence, each takes the opportunity to reevaluate his or her life and re-establish their bonds.